Factors inhibiting local government engagement in environmental sustainability - Wild River, S.; Pini, B.; McKenzie, Fiona Haslam (Australian Geographer, 2007)
The literature on local government management of the environment in Australia has been limited in that it has typically focused on the urban sphere. In contrast, this paper places rurality at the centre of its inquiry. It uses data from 15 case studies of rural local governments in Australia to identify the main factors that inhibit natural resource management by rural councils. These barriers mobilise around four key themes: capacity, commitment, co-ordination and community. While many of the issues raised in this study of non-urban shires have been described in previous research, the paper argues that the geographic location of the areas under investigation aggravates barriers to engaging sustainability initiatives. It is contended that rural local governments need to be resourced accordingly to ensure that natural resource management at the local government level in Australia is not compromised.